Analisis Kompetensi Mahasiswa Program Studi Sekretari dalam Praktik Kerja Lapangan - Siti Umi Khayatun Mardiyah; Joko Kumoro; Chusnu Syarifa Diah Kusuma; Wahyu Rusdiyanto (Efisiensi : Kajian Ilmu Administrasi, 2018)
Abstrak: Analisis Kompetensi Mahasiswa Program Studi Sekretari dalam Praktik Kerja Lapangan. Tujuan dari penelitian ini adalah: 1) Mengetahui tanggapan Dunia Usaha/Dunia Industri (DU/DI) tentang kompetensi mahasiswa Program Studi (Prodi) D3 Sekretari Fakultas Ekonomi Universitas Negeri Yogyakarta (FE UNY); 2) Mengetahui kompetensi sekretaris yang dibutuhkan oleh DU/DI. Penelitian dilaksanakan bulan Juli sampai dengan Agustus 2017. Penelitian ini merupakan  penelitian deskriptif. Pengumpulan data menggunakan kuesioner tertutup dan terbuka. Populasi penelitian adalah organisasi/perusahaan yang menjadi tempat Praktik Kerja Lapangan (PKL). Penarikan sampel penelitian menggunakan teknik purposive sampling. Analisis data penelitian ini menggunakan tahap-tahap analisis data sebagai berikut: 1) mengorganisasi data dan melakukan pemeriksaan data dengan cermat, 2) melakukan pemeriksaan ulang terhadap data, 3) melakukan pengolahan data, 4) melakukan analisis terakhir, membuat interpretasi dan kesimpulan akhir. Hasil penelitian menunjukkan bahwa: 1) tanggapan sebagian besar DU/DI terhadap aspek pengetahuan mahasiswa masuk dalam kategori baik. Aspek keterampilan mendapatkan tanggapan baik. Aspek kepribadian mendapatkan tanggapan baik. 2) Usulan kompetensi baru yang perlu dikuasai oleh calon sekretaris, pihak DU/DI menitikberaktan pada kompetensi yang berkaitan dengan penguasaan teknologi informasi dan internet.  ABSTRACT: Analysis of Office Graphic Design Skills for Diploma Students of Secretary Program in Yogyakarta Sate University. One of the secretary roles is as an executor of public relations functions, so that a prospective secretary is required to have the skills to design publications. This study aims to: 1) Know the response of the business/industrial about the needs of office graphic design skills for diploma students of the Secretariat FE UNY; 2) Knowing the graphic design skills needed by business / industrial. The study was conducted in April-June 2018. This study used a descriptive research design with a quantitative approach. The research data was taken using a closed questionnaire. The population in this study were D3 Secretariat students of the UNY FE and organizations or companies that became the place of Field Work Practices (PKL) of D3 Students Secretariat of the Faculty of Economics UNY. The withdrawal of the study sample used a purposive sampling technique for respondents from the DU / DI group and incidental sampling techniques for respondents from the D3 student group at the UNY FE Secretariat. The results showed that the responses of most DU / DI and students regarding the needs of office graphic design skills were: 1). Office graphic design skills are the skills of modern office administration needed to deal with the modernization and variation of office work; 2). The most widely used media delivery information in business/industrial is X-banner; 3). Submission of information looks more modern, interesting and informative with office graphic design skills; 4). Office graphic design skills for students and employees are considered important to be mastered; 5). office graphic design products for the most chosen modern office work, namely agency / company logos. The results of this study can be used as material for consideration and recommendations for the formulation of the UNY FE Secretariat Diploma curriculum and other vocational schools that have similar scientific nomenclature.